Enhancing Pre-Service Mathematics Teachers' Competencies in Distance Education: An Empirical Investigation Utilizing Micro-Teaching and Peer Assessment - Saralar-Aras, Ipek; Gunes, Habibe (Springer, 2025)
The COVID-19 pandemic has prompted pre-service teachers to assume various teacher roles in distance education, necessitating a diverse range of competencies. However, pre-service mathematics teachers have expressed the need for professional support to enhance their preparation for future teaching responsibilities. This study explores the impact of a designed training program on pre-service mathematics teachers' self-assessment of their knowledge regarding teacher roles in distance education. The training course comprised seven sessions dedicated to instructional design, technology integration, pedagogical strategies, classroom management, facilitation, social interaction, and evaluation. Additionally, three sessions provided support for participants in designing their micro-teaching activities, followed by four sessions of micro-teaching with peer assessment. Data collected through questionnaires, interviews, micro-teaching materials, and rubrics were analysed using t-tests and content analysis. The results demonstrate that the implemented training program, incorporating micro-teaching and peer assessment, significantly enhanced pre-service mathematics teachers' perceived competence in various teacher roles. Consequently, we recommend the integration of these methods into teacher training programs as valuable pedagogical approaches.
Keywords: Distance education; Micro-teaching; Peer assessment; Preservice maths teacher